LNA-anti-miR-150 alleviates renal interstitial fibrosis by reducing pro-inflammatory M1/M2 macrophage polarization - Hao, Xiangnan; Luan, Junjun; Jiao, Congcong; Ma, Cong; Feng, Zixuan; Zhu, Lingzi; Zhang, Yixiao; Fu, Jingqi; Lai, Enyin; Zhang, Beiru; Wang, Yanqiu; Kopp, Jeffrey B.; et al. (Frontiers in Immunology, 2022)
Renal interstitial fibrosis (RIF) is a common pathological feature contributing to chronic injury and maladaptive repair following acute kidney injury. Currently, there is no effective therapy for RIF. We have reported that locked nuclear acid (LNA)-anti-miR-150 antagonizes pro-fibrotic pathways in human renal tubular cells by regulating the suppressor of cytokine signal 1(SOCS1)/Janus kinase (JAK)/signal transducer and activator of transcription (STAT) pathway. In the present study, we aimed to clarify whether LNA-anti-miR-150 attenuates folic acid-induced RIF mice by regulating this pathway and by reducing pro-inflammatory M1/M2 macrophage polarization. We found that renal miR-150 was upregulated in folic acid-induced RIF mice at day 30 after injection. LNA-anti-miR-150 alleviated the degree of RIF, as shown by periodic acid Schiff (PAS) and Masson staining and by expression of pro-fibrotic proteins, including alpha-smooth muscle actin and fibronectin. In RIF mice, SOCS1 was down-regulated and p-JAK1 and p-STAT1 were up-regulated. LNA-anti-miR-150 reversed the changes in renal SOCS1, p-JAK1 and p-STAT1 expression. In addition, renal infiltration of total macrophages, pro-inflammatory M1 and M2 macrophages, as well as their secreted cytokines, were increased RIF mice compared to control mice. Importantly, in folic acid-induced RIF mice, LNA-anti-miR-150 attenuated renal infiltration of total macrophages and pro-inflammatory subsets, including M1 macrophages, expressing CD11c and M2 macrophages, expressing CD206. We conclude that the anti-renal fibrotic role of LNA-anti-miR-150 in folic acid-induced RIF mice may be mediated by reducing pro-inflammatory M1 and M2 macrophages polarization via the SOCS1/JAK1/STAT1 pathway.